Effect of parenteral amino Acid supplementation in preterm low birth weight newborn - Alo, D; Shahidullah, M; Mannan, MA; Noor, K (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Jul;19(2):386-90 The abstract of this article is available on the PubMed website